2023
DOI: 10.1039/d2gc03392e
|View full text |Cite
|
Sign up to set email alerts
|

A multienzyme biocatalytic cascade as a route towards the synthesis of α,ω-diamines from corresponding cycloalkanols

Abstract: A multienzymatic cascade for the synthesis of 1,6-Hexamethylenediamine (HMD) and related α, ω-diamines from corresponding cycloalkanols is reported herein. In this work, an E coli-based modularization strategy was applied to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…As mentioned above, pyruvate generated by glycolysis can be detrimental to transamination, leading to the deamination of the produced amine compounds. As a resolution of this, it was previously reported that point mutagenesis of an arginine residue in the active site of a transaminase causes loss of pyruvate acceptance, resulting in the improvement of short-chain amine compounds . To verify this, we first developed TA-PLP conjugate structures through homology modeling (Figure S14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, pyruvate generated by glycolysis can be detrimental to transamination, leading to the deamination of the produced amine compounds. As a resolution of this, it was previously reported that point mutagenesis of an arginine residue in the active site of a transaminase causes loss of pyruvate acceptance, resulting in the improvement of short-chain amine compounds . To verify this, we first developed TA-PLP conjugate structures through homology modeling (Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…As a resolution of this, it was previously reported that point mutagenesis of an arginine residue in the active site of a transaminase causes loss of pyruvate acceptance, resulting in the improvement of short-chain amine compounds. 46 To verify this, we first developed TA-PLP conjugate structures through homology modeling (Figure S14). Next, we found target residues in interaction with the amine donor (benzylamine) and pyruvate, respectively, considering the possible hydrogen bonds.…”
Section: The Production Of αω-Diamines With Varying Carbon Chain Leng...mentioning
confidence: 99%
“…Notably, the only variable was the addition of glucose, which plays an important role in regenerating co-factors needed by CAR through the action of intracellular enzymes (Napora-Wijata et al, 2014). Since it is understood that glucose metabolism in resting whole cell biocatalysts generates substantial amounts of alternative amine acceptors such as pyruvate and ketoglutarate (Supporting Information: Figure S3a ) (Sarak et al, 2022), we looked at the influence of glucose concentration on the ability of WC2 to convert 1b. We saw that this was impaired at glucose concentrations of 55 mM and 110 mM (Supporting Information: Figure S3b ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the only variable was the addition of glucose, which plays an important role in regenerating co‐factors needed by CAR through the action of intracellular enzymes (Napora‐Wijata et al, 2014). Since it is understood that glucose metabolism in resting whole cell biocatalysts generates substantial amounts of alternative amine acceptors such as pyruvate and ketoglutarate (Supporting Information S1: Figure 3a) (Sarak et al, 2022), we looked at the influence of glucose concentration on the ability of WC2 to convert 1b. We saw that this was impaired at glucose concentrations of 55 and 110 mM (Supporting Information S1: Figure 3d).…”
Section: Resultsmentioning
confidence: 99%